A STUDY OF THE ULTRASTRUCTURE OF THE SURFACE OF THE TRANSPLANTABLE LINE VERO CELLS INFECTED WITH THE RABIES VIRUS (RABV, LISSAVIRUS, RHABDOVIRIDAE) - S. V. Generalov; P. S. Erokhin; T. Yu. Krasovskaya; N. A. Osina; E. G. Abramova; A. K. Nikiforov; S. A. Shcherbakova (Вопросы вирусологии, 2017)
Characteristics of the effect of attenuated rabies virus strain «Moscow 3253» on morphological parameters of transplantable line Vero cells were studied by atomic force microscopy (AFM). Methods based on phase contrast microscopy and immunofluorescence were used to confirm the specificity of interaction and to identify the infectious activity of the rabies virus. Images of intact Vero cells and Vero cells infected with rabies virus were obtained at different periods of cultivation. The character of changes in the cell dimensions (length, width, height) and the cell membrane roughness depending on the rabies virus cultivation time was determined. During the observation period both increases and decreases in the size of the cells were recorded. The size of the infected cells exceeded that of the intact. An increase in the membrane roughness in cells exposed to rabies occurred during the entire period of observation, since the first hours of the interaction of the virus with the cell, while the intact Vero cells exhibited only minor changes in the membrane surface roughness, which were not dependent on the age of the culture. The dependence of the increase in the cell membrane roughness on the infecting dose of the rabies virus was determined. The obtained results open up the prospect of developing a methodological approach to the quantitative in vitro evaluation of the rabies virus using AFM. Changes in the cell membrane roughness appear to be the most indicative parameter for such evaluation.